TINJAUAN YURIDIS PERATURAN OTORITAS JASA KEUANGAN NOMOR 55/POJK.05/2017 TENTANG LAPORAN BERKALA PERUSAHAAN PERASURANSIAN - Ashari, Imam Edy (Nusantara Hasana Journal, 2022)
This research is entitled Juridical Review of Financial Services Authority Regulation Number 55/Pojk.05/2017 concerning Insurance Company Periodic Reports. The purpose of this research is to find out what are the functions, duties, and authorities of the Financial Services Authority related to insurance and to know the mechanism of the insurance company's periodic reports to the Financial Services Authority. The research method used is descriptive qualitative with normative juridical research, data collection techniques used are literature study and data analysis using qualitative analysis. The results of the research show that OJK functions to organize an integrated regulatory and supervisory system for all activities in the financial services sector. To carry out regulatory and supervisory duties in the insurance sector, OJK has the authority to: a. To stipulate the implementing regulations of this Law; b. To stipulate laws and regulations in the financial services sector; c. To stipulate OJK regulations and decisions; d. Establish regulations regarding supervision in the financial services sector; e. Establish policies regarding the implementation of OJK duties; f. To stipulate regulations regarding procedures for determining written orders against Financial Services Institutions and certain parties; g. To stipulate regulations regarding procedures for determining statutory managers at Financial Services Institutions; h. Establish organizational structure and infrastructure, as well as manage, maintain, and administer assets and liabilities; and i. Establish regulations regarding procedures for imposing sanctions in accordance with the provisions of laws and regulations in the financial services sector. Insurance Companies are required to submit Periodic Reports to the Financial Services Authority in the form of: a. Monthly Reports, Quarterly Reports, Semester Reports, and Other Reports that are submitted in accordance with the provisions stipulated in the Financial Services Authority Regulation or other laws and regulations that require the submission of the said report; and b. The Annual Report is submitted no later than April 30 of the following year. If the deadline for submitting reports falls on a holiday, the deadline for submitting reports is the first working day following an Insurance Company that does not prepare and submit Periodic Reports completely and on time in accordance with the provisions of the Financial Services Authority Regulations in Article 2 paragraph (1) and Article 8 paragraph (1) is subject to administrative sanctions (which are carried out in stages) in the form of27: a. Written warning; b. Restrictions on business activities, for part or all of business activities; and/or c. Revocation of business license.